2018
DOI: 10.1111/ajt.14562
|View full text |Cite
|
Sign up to set email alerts
|

OPTN/SRTR 2016 Annual Data Report: Lung

Abstract: In 2016, 2692 candidates aged 12 years or older were added to the lung transplant waiting list; 2345 transplants were performed, the largest number of any prior year. The median waiting time for listed candidates in 2016 was 2.5 months, and waiting times were shortest for group D candidates. The transplant rate increased to 191.9 transplants per 100 waitlist years in 2016, with a slight decrease in waitlist mortality to 15.1 deaths per 100 waitlist years. Short-term survival continued to improve, with a 6-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(97 citation statements)
references
References 0 publications
1
95
0
1
Order By: Relevance
“…This survey analysis showed that more non-kidney transplant candidates (liver, heart, and lung) were willing to accept an HCV-positive organ compared to kidney transplant candidates, although this difference was not statistically significant (p = 0.05). This difference may indicate that the lack of a suitable alternative such as dialysis for the end-stage disease of these organs (although left ventricular assist devices are being used for heart failure) coupled with higher waitlist mortality rates may lead non-kidney transplant candidates toward pursuing HCV-positive organ transplantation more eagerly [2,3,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…This survey analysis showed that more non-kidney transplant candidates (liver, heart, and lung) were willing to accept an HCV-positive organ compared to kidney transplant candidates, although this difference was not statistically significant (p = 0.05). This difference may indicate that the lack of a suitable alternative such as dialysis for the end-stage disease of these organs (although left ventricular assist devices are being used for heart failure) coupled with higher waitlist mortality rates may lead non-kidney transplant candidates toward pursuing HCV-positive organ transplantation more eagerly [2,3,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Despite stringent selection criteria and advances in surgical and medical therapies, mortality after lung transplantation is high and has not improved in the last 5 years (1). …”
Section: Introductionmentioning
confidence: 99%
“…While achieving its primary aim, a consequence of the Lung Allocation Score (LAS) system is that older and sicker candidates are prioritized for transplantation. As a result, older adults (age ≥65) are the fastest growing group of lung transplant candidates in the U.S., now accounting for nearly 30% of new transplant recipients compared to only 4% in 2002(1). After lung transplantation, those 65 years and older have a median survival of only 3.6 years, fully three years less than those 35–49 years old (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the field of lung transplantation has evolved considerably since the first lung transplant with long-term success was performed in 1983,1 the need for donated lungs to help patients with progressive end-stage lung diseases that do not respond to non-transplant therapies continues to outstrip the availability of lungs from organ donors 2. Many patients with certain types of lung disease or other characteristics such as short stature or ABO blood type O may be less likely to receive an organ offer than those with different profiles and are, therefore, more at risk to die while waitlisted and awaiting lung transplantation 3 4.…”
mentioning
confidence: 99%